An explorative study of linear vs non-linear hedonic pricing of second-hand cars in South Africa - Hendry, Stuart (School of Management Studies, 2025)
This study investigates the pricing dynamics of the top four entry-level used cars in South Africa, namely the Ford Fiesta, Hyundai i10, Toyota Etios, and VW Polo Vivo. Using a hedonic pricing approach to develop four linear and four non-linear regression models the study analyses a comprehensive dataset of 4,386 second-hand vehicles collected from the Cars.co.za website in 2018 and focuses on eight key vehicle attributes, namely age, mileage, region (province of origin), transmission type, fuel type, colour, engine size, and sub-model variant. The use of hedonic pricing theory enables the deconstruction of overall vehicle price into marginal contributions of the eight attributes, thereby offering a detailed understanding of their marginal, relative value in determining fair market prices. For instance, characteristics such as age and mileage exhibited diminishing returns, highlighting that their impact on price decreases disproportionately as values increase. The research identifies asymmetrical relationships between vehicle price and its attributes through a comparative analysis of linear and non-linear regression models. The non-linear models, enhanced by the inclusion of dummy variables, outperformed linear models in terms of accuracy, offering a more precise tool for identifying value for money in the second-hand car market. This study integrates strategic marketing, and applied management elements to provide actionable insights for stakeholders across the used-car sector, including consumers, dealers, insurers, and manufacturers. The statistical analysis within an applied management framework is exploratory and the findings equip consumers with knowledge for making more informed purchasing decisions and assists dealers and insurers in refining pricing strategies and product offerings. Manufacturers are also advised to prioritize attributes significantly impacting resale value during the design and production phases. In light of increasing digitalization and technological disruptions, the study advocates for the development of a consumer-facing digital platform that incorporates hedonic pricing models. This would offer consumers a reliable tool to evaluate and compare used-car prices in an increasingly complex market and promote trust between buyers and sellers.